2004
DOI: 10.1111/j.1741-4520.2003.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Position‐specific expression of Hox genes along the gastrointestinal tract

Abstract: Hox genes play a critical role in morphogenesis of the early embryo along the anteroposterior axis. In mammals, 39 Hox genes with extensive homology are organized into 13 paralogous groups, forming four clusters on four separate chromosomes. The genes within each cluster are arranged in a 3' to 5' direction and expressed in a temporally and spatially coordinated manner along the anteroposterior axis in the vertebrae, limbs and viscera, including the gastrointestinal tract, but little is known about their spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Of note, we found high expression levels of midcluster HOXB genes also in BE cases with no histological evidence of globet cells, in keeping with the notion that a pathological diagnosis of BE can be supported by both gastric and intestinal metaplasia (35). With regards to HOXB gene levels in normal gut epithelia, our data are in agreement with previous evidence that midcluster HOXB genes are less expressed in the esophagus than in posterior segments of the GI tract (21). However, the midcluster HOXB profile we found in human adult GI tissues does differ from that found in embryonic murine gut (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, we found high expression levels of midcluster HOXB genes also in BE cases with no histological evidence of globet cells, in keeping with the notion that a pathological diagnosis of BE can be supported by both gastric and intestinal metaplasia (35). With regards to HOXB gene levels in normal gut epithelia, our data are in agreement with previous evidence that midcluster HOXB genes are less expressed in the esophagus than in posterior segments of the GI tract (21). However, the midcluster HOXB profile we found in human adult GI tissues does differ from that found in embryonic murine gut (22).…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of markers of intestinal differentiation and CDXs (5,20), little is known about similarities in gene-expression patterns between BE and other normal gut epithelia. In addition only one study has looked at HOX expression levels in the human adult gut (21). We tested the expression of midcluster HOXB genes also in other normal gastrointestinal (GI) epithelia, such as stomach, duodenum, and colon ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, Yahagi and colleagues (9) showed that HOX genes with high expression in the foregut had a propensity for low expression in the hindgut, whereas those with a low expression in the foregut tended to have high expression in the hindgut. Specifically, paralogue 13 (HOXA13, HOXB13, and HOXD13) had a tendency for high expression in the hindgut region and weak expression in the foregut including the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Malfunctioning and dysregulation of these genes during development lead to innate deformities and malformations (Dolle et al 1993a;Mark et al 1997;Zakany et al 1997). Dysregulation of HOX genes in adult tissue has been directly linked with cancer and tumorigenesis Yahagi et al 2004;Grier et al 2005). Our understanding of the role of HOX genes has mostly relied on animal models and, therefore, remains limited in normal and diseased human tissues (Johnson 1914;Kluth et al 1995).…”
Section: Introductionmentioning
confidence: 99%